Professional presentations - Bampfield, Andrew (Cambridge : Cambridge University Press, 1998)
It shows an opportunity for students to reflect on the dos and don'ts of presentations and also shows an authentic presentations of a hi-fi company's products
Writer, Malcolm Goodale
Keywords: Public speaking; Oral communication